Chemical and biological analyses of Malaysian stingless bee propolis extracts - Abd Jamil, Zakaria; Khamsah Suryati, Mohd; Nurhamizah, Ibrahim (Malaysian Society of Analytical Sciences, 2016)
The aim of this study is to evaluate chemical and biological profile of methanol extracts from Malaysian propolis produced by two commonly found stingless bee species, Heterotrigona itama (MHI) and Geniotrigona thoracica (MGT). Test samples were analyzed for physicochemical parameters such as moisture, fat, crude fibre, crude protein, carbohydrate and ash content. Tests for phytochemical screening by thin layer chromatography of both extracts revealed that presence of terpenoids, flavonoids, phenols and essential oils but steroids, saponin and coumarins only occur in MHI. Both extracts displayed a characteristic profile and vary from each other. Accordingly, MHI possess higher antioxidant activity with an IC50 of 15.0 ± 0.21 ug/mL compared to MGT with IC50 of 270.0 ± 0.19 ug/mL. MHI showed moderate nitric oxide scavenging activity, while MGT only showed mild inhibition. Antidiabetic activity was determined by α-glucosidase inhibition and found significantly better than that of acarbose (positive control). In conclusion, data gathered in this study revealed that bee species play role in determining the chemical and biological profile of particular propolis and should put into account in decision of further development for propolis.